Analisis Hukum Jual Beli Rumah Over Credit di Bawah Tangan Perspektif Sadd Adz-Dzari’ah: Studi Kasus Perumahan Griya Madani, Desa Parbangunan, Kecamatan Panyabungan, Kabupaten Mandailing Natal - Apriani, Rizki Dina; Sahliah (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study is motivated by the widespread practice of unofficial over-credit house sales, particularly in the Griya Madani Housing Complex, Parbangunan Village, Panyabungan Sub-district, Mandailing Natal Regency. The aim of this research is to analyze the legality of unofficial over-credit house transactions from the perspective of sadd adz-dzari’ah. This study employs an empirical juridical method with a case study approach. Primary data were obtained through interviews and direct observation, while secondary data were collected from literature reviews. The findings reveal that there have been seven unofficial over-credit transactions in the Griya Madani Housing Complex. Contributing factors include the avoidance of high bank administrative fees, faster and simpler processes, and greater financial benefits compared to purchasing a new house. The sadd adz-dzari’ah analysis identifies several potential harms (mafsadat), such as legal uncertainty regarding property ownership, the risk of fraud or default, breach of contract with the bank, financial losses for the bank as the creditor, and the absence of legal protection for the new buyer. Based on the principles of sadd adz-dzari’ah, such transactions fall into the category of harmful means that should be prevented due to the greater harm than benefit they pose. This study recommends that such transactions be conducted through official credit transfer mechanisms involving banks and notaries to ensure legal certainty and prevent detriment to all parties involved.